Effect of Low-Temperature Degradation, Ph-Cycling and Simulated Tooth Brushing on Surface Roughness, Topography, and Polish Retention of Yttrium-Stabilized Tetragonal Zirconia - Foroogh Fadavi; Mahshid Mohammadi-Bassir; Nioosha Sarabi; Mohammad Bagher Rezvani; Siavash Jafari-Semnani; Maryam Rastegar Moghaddam; Hossein Labbaf (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Surface roughness of zirconia is an important parameter that determines the success of zirconia restorations. When zirconia surfaces are left rough, higher susceptibility to hydrothermal aging, plaque accumulation and color changes would occur. Therefore, polish retention of these restorations is considered as a challenge.Purpose: The purpose of this in vitro study was to determine the effect of hydrothermal degradation, pH- cycling, and simulated tooth brushing on surface roughness, topography, and polish retention of an yttrium-stabilized monolithic zirconia.Materials and Method: In this experimental study, 64 specimens of yttria-stabilized tetragonal zirconium oxide (20×4×2mm) were prepared (ZirKonzahn, Steger, Ahrntal). The specimens were wet- polished (standard polishing), and divided into 8 groups (n=8). Four control groups were assessed in non-aged condition while in 4 experimental groups the artificially ageing was done. Different finishing and polishing procedures were performed in 8 groups. The surface roughness values including mean surface roughness (Ra) and mean height of surface roughness (Rz) was measured by a profilometer. The results were analyzed using two-way ANOVA and Tukey's HSD test (α=0.05). One representative specimen of each group was inspected under a scanning electron microscope (SEM) for assessment of surface topography.Results: The effects of surface treatments on Ra (p<.001) and Rz (p<.001) parameters were significant. Ageing had no significant effect on Ra (p=.086) and Rz (p=.067) values. Maximum Ra and Rz parameters were recorded following grinding (p<.001) and minimum values were recorded after glazing, which were significantly lower than the values in grinding group (p<.001). Polishing and glazing diminished the surface roughness (Ra) of ground zirconia similarly (p=.995).Conclusion: Aging had no significant effect on surface roughness of zirconia, irrespective of surface treatment type. Grinding yielded maximum surface roughness. Intra oral polishing yielded a surface roughness comparable to standard polishing and glazing.